Pengaruh Pembelajaran Berdiferensiasi, Motivasi Belajar, Dan Lingkungan Keluarga Terhadap Kemampuan Berpikir Kritis Siswa Di SMKN 1 Jeneponto - Amanda Ratu Auliah; Rahmatullah Rahmatullah; Ratnah Suharto; Sri Hutami Adiningsih; Muh Ilyas Thamrin Tahir (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study was designed to examine the role of differentiated learning, learning motivation, and family environment in shaping students' critical thinking skills at SMKN 1 Jeneponto. This study was conducted using a quantitative approach and an associative descriptive research design to systematically describe the relationship between variables. Accounting students in grades X and XI were all selected as respondents using a saturated sampling technique. Data were analyzed using the PLS-SEM approach assisted by SmartPLS to test the relationship between variables, including direct and indirect effects. The research findings indicate that differentiated learning, learning motivation, and family environment contribute to the development of critical thinking skills. The family environment is the main element that contributes greatly to strengthening students' critical thinking skills, while differentiated learning and learning motivation strengthen cognitive and reflective analysis processes. Overall, students' critical thinking skills are influenced by the synergy of adaptive learning implementation, strong intrinsic motivation, and consistent family support in creating a conducive and inspiring learning environment